Future railway mobile communication system automated planning - Queirós, Artur Daniel Rocha (2023)
With the end of support for the Global System for Mobile Communications Railway (GSM-R) in sight, there needs to be a change in the technology used in railway communications. To achieve this, operators began the transition to Future Railway Mobile Communication System (FRMCS). The work developed in this thesis demonstrates the application of the concept of ge netic algorithms in a telecommunications network planning. Where the objective is to understand whether the results obtained are viable comparing to the currently practiced values. To achieve this, it is necessary to develop an algorithm that allows to obtaining the best possible solution for the placement of antennas along the line in the most efficient way, taking into account its coverage. The work developed includes the construction of this same algorithm and all its phases.Using the Cascais line as a test subject and with the help of data made available by the company Solvit, it is possible to obtain different scenarios varying four parameters, the population size, the number of generations, the crossover probability and the mutation probability. The final results prove that the use of genetic algorithms to optimize a railway telecommunications network can be a useful and powerful tool, as the results obtained presents an optimized value compared to the current solution used by public operators.